A study on the flow behavior and bubble evolution of circular oscillating laser welding of SUS301L-HT stainless steel. (March 2023) - Zhao, Xu; Chen, Jintao; Lei, Zheng; Zhang, Weihua; Chen, Hui
Abstract: The flow characteristics, bubble formation and inhibition mechanisms of circular oscillating laser beam welding (OLBW) at distinct stages were elucidated in present work. The formation processes of bubbles mainly included the following manners. First, one or more of vortex P2, the recoil pressure flow P3, the migration flows FMF and BMF impinged the keyhole wall. The necking generated, gradually destabilized, and finally collapsed. Second, the self-instability of needle-like keyhole bottom (NKB) with large curvature induced the bubble formation. Third, complex melt flow broke the abnormal deformation of the keyhole or the bubble wall to form a new bubble. The bubble suppression mechanisms were summarized to three categories. First, the recoil pressure on the inner wall of bubble was at a low level, and the volume of bubble continually decreased until it collapsed. Second, high recoil pressure penetrated the metal liquid bridge between keyhole and bubble. Third, when recoil pressure was greater than the resultant force between surface tension and melt dynamic pressure, the bubble constantly fluctuated and gradually merged with the moving keyhole. As the frequency increased from 10 Hz to 200 Hz, porosity showed an exponential decrease from 7.16% to 0.35% in circular oscillation mode. A unified porosity prediction curve based on the Reynolds number was built with a coefficient of determination of 0.989. When fluid changed from laminar to turbulent flow, the critical Reynolds number was set as 1000, the predicted porosity was 0.912%, and the critical frequencies in circular and infinite oscillation modes were 143 Hz or 115 Hz, respectively, which were consistent with experiment results.